Analysis of the Use of the Merdeka Mengajar Platform Using the Hedonic Motivation System Adoption Model - Djusar, Syahtriatna; Abini, Eka Yestira Nita; Asril, Elvira; Zamsuri, Ahmad (Universitas Negeri Semarang, 2024)
The success of the implementation of the Merdeka Mengajar Platform (PMM) is measured by its acceptance and sustained use by teachers. This study will measure the factors influencing the acceptance and continued use of PMM by 53 teachers as respondents, from four high schools in the Rumbai District of Pekanbaru City, Riau Province, each of whom was given 21 questions. To accomplish this, the Hedonic Motivation System Adoption Model was used, which includes the following variables: Perceived Ease of Use (X1), Perceived Usefulness (X2), Curiosity (X3), Joy (X4), Control (X5), Behavioral Intention to Use (Y1), and Focused Immersion (Y2). Data analysis was conducted using Validity Tests, Reliability Tests, Normality Tests, Linearity Tests, Correlation Tests, Partial Tests, Simultaneous Tests, and Hypothesis Tests. The aspects derived from the use of PMM indicate that the hedonic factors for ease of use (X1) and curiosity (X3) in relation to intention (Y1) have correlation values of 0.560 and 0.661, respectively. Ease of use (X1) has full control over joy (X4) in relation to intention (Y1), with correlation values of 0.560 and 0.657. The factors influencing the success of PMM acceptance are curiosity (X3) and joy (X4). The higher the ease of use combined with curiosity and joy, the stronger the intention to use the application.